Studying strategy from a practice perspective: an overview and examples - Clegg, Stewart (Henry Stewart Talks, 2012)
What is strategy, Strategy is political, Rationality and strategy, Strategy and practice, Origins, Strategy process, Key S-as-P questions, Strategy in the city, Data, Case study of Sydney, Strategizing, politics and the public